IDENTIFIKASI DAN MONITORING GANGGUAN LAYANAN FIBER OPTIK MENGGUNAKAN APLIKASI FIELD SUPPORT MANAGEMENT DAN XSHELL 7 - Firgiawan Prasetya, I Putu; Sukadarmika, Gede; Diafari Djuni H, IGAK (Jurnal SPEKTRUM, 2022)
The need and demand for reliable telecommunication services is one of the most important needs of today’s society. One way to realize this need is to use fiber optic services as a data transmission medium from the center of the provider to customer’s house. The purpose of this study was to assist the field team to check the condition of the device before and after recovery when there are disturbance in fiber optic service. Using Field Support Management and XShell 7 application can resolve and make it easier to identify and monitor if there are disturbances that occur in fiber optic service. The disturbance or interference that occurs can be in the form of a broken fiber optic cable, or a problem with the ONT device on the user side. The desired power receive limit is -27 dBm, because the power received will affect the quality of data service obtained on the user side.